Modern Rivularia Freshwater Stromatolites as Models for Formation of Laminated Stromatolitic Crusts. Issue 4 (3rd April 2023) - Hoppert, M.; Reimer, A.; Sauter, K.; Reitner, J.
Abstract: In the present study, microbialites from a stream in the Ammergau Alps (Northern Calcareous Alps) were examined with regard to morphology, mineralogy, and colonizing microorganisms. The carbonate buildups form regular (mainly laminated) stromatolite structures, essentially due to the activity of the cyanobacterium Rivularia . The filaments of the cyanobacterium form exopolymer sheaths that prevent the precipitation of calcite from the carbonate-supersaturated stream water at cell surfaces. A pattern of non-calcified, parallel tubes surrounded by a calcified scaffold is built up. The calcification pattern may be explained by the inhibitory activity of cyanobacterial sheath exopolymers. In lower layers of the carbonate buildup, microbial diversity increases due to colonization by mainly heterotrophic bacteria. The hollow tubes hitherto exempt from calcification are gradually being filled. Calcification pattern is discussed in view of fossil Girvanella -type stromatolites.